Sorting through the pediatric MS spectrum with brain MRI - Chabas, Dorothée; Pelletier, Daniel (Nature reviews. Neurology, 2009)
Distinguishing between a first episode of multiple sclerosis and acute disseminated encephalomyelitis in children who present with an initial demyelinating event can be a clinical challenge. New brain MRI criteria that aim to differentiate these clinical presentations, and revised McDonald MRI criteria specific for the pediatric population, are both worthy of note.